South Batak Tradition for the Settlement of Environmental Disputes: A Tumbaga Holing Letter Model - HARAHAP, Anwar Sadat; MULYONO, Hardi; HASIBUAN, Ahmad laut; SIREGAR, Taufik (Journal of Environmental Management and Tourism; Vol 12 No 7 (2021): JEMT Volume XII, Issue 7(55), Winter 2021, 2021)
In recent years, there has been a lot of environmental destruction caused by human activities, such as: dumping garbage into rivers, lakes, seas, public roads and others. A series of environmental crimes arise because less firm of existing legal regulation on environmental protection. To seek the new model of environmental protection, an empirical research method with a normative juridical approach and a socio-legal approach were applied. The results of the study show that the South Batak community, based on intangible heritage, has a convention to protect nature and people from disaster and Sociological it was already applied for the environmental disputes resolution; it is through convention of South Batak of Tumbaga Holing Letter of Dalihan na Tolu (a tree parted system in community meeting). South Batak community practices a manifestation of the implementation of justice against the perpetrators of acts of environmental destruction with 7 (seven) types of sactions. The seventh sactions range from the low to hard punishments. It is a traditional model that can be adopted into the modenr regulation, public policy or laws for environmental protection. It found that the South Batak Comunity model in prevention of environment desctruction has a lot of elements of the judiciary that could be adopted and implementated for public policy and law making in national and international levels.